PREVENTING TOKENISM IN THE FORMATION OF LEGISLATION THROUGH MEANINGFUL PUBLIC PARTICIPATION - Windy Virdinia Putri; Gumilang Fuadi; Nanik Prasetyoningsih (Domus Legalis Cogitatio, 2024)
The Constitutional Court Decision Number 91/PUU-XVIII/2020 expands the meaning of public participation, namely that public participation in forming laws needs to be carried out meaningfully. The discussion about public participation is closely related to the relationship between the community and the state in forming policies that the state will issue to regulate its citizens. This paper analyzes the arrangements for meaningful public participation after the second amendment to Law Number 12 of 2011 concerning the Formation of Legislation (UUP3) with two objectives, first to find out the arrangements for meaningful public participation after the second amendment to UUP3 from the perspective of the Arnstein Participation Ladder. Two to knowing the meaning of meaningful public participation so as not to be in the area of ​​tokenism. The results of the study show that the regulation of public participation is in the area of ​​tokenism because there is no guarantee that decision-makers will accommodate the voice of the community. The way to increase public participation while at the same time encouraging community involvement far beyond tokenism is to arrange a public sphere mechanism for public debate to occur as the basis for drafting the National Legislation Program.